Global warming and urbanization - Marc Helbling; Daniel Meierrieks (Journal of Population Economics, 2022)
Analyzing 118 countries between 1960 and 2016, we find that higher temperatures correlate with higher urbanization rates in the long run, where this relationship is much more pronounced than any short-term linkage. The long-run relationship between global warming and urbanization is also conditional upon country-specific conditions. This long-run association is especially relevant in poorer and more agriculture-dependent countries with an urban bias as well as in initially non-urban countries in hotter climate zones. We also provide suggestive evidence that warming contributes to losses in agricultural productivity and to pro-urban shifts in public goods provision and that the global warming-urbanization nexus is partly mediated through these channels. Consequently, we argue that the estimated long-run relationship between temperature and urbanization partly captures the potential impact of increasing temperatures on urbanization via a rural push (by impairing agriculture) and an urban pull (via an increased demand for public goods primarily supplied in cities).
Keywords: Q54; R23; 330; climate change; global warming; urbanization; rural–urban migration; panel vector error correction models